2014
DOI: 10.1051/epjconf/20147100095
|View full text |Cite
|
Sign up to set email alerts
|

Energy loss in unstable QGP - problem of the upper cut-off

Abstract: Abstract. The energy loss of a highly energetic parton in a weakly coupled quark-gluon plasma is studied as an initial value problem. An extremely prolate plasma, where the momentum distribution is infinitely elongated along one direction, is considered. The energy loss is strongly time and direction dependent and its magnitude can much exceed the equilibrium value. It is logarithmically ultraviolet divergent. We argue that a good approximation to the energy loss can be obtained if this divergence is cut off w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…which is often more convenient to use than the expression (24). The energy loss in equation ( 10) can now be written in terms of the Fourier transformed field and current.…”
Section: General Formulamentioning
confidence: 99%
See 2 more Smart Citations
“…which is often more convenient to use than the expression (24). The energy loss in equation ( 10) can now be written in terms of the Fourier transformed field and current.…”
Section: General Formulamentioning
confidence: 99%
“…In these reports, we used a specific choice of initial conditions and we were not aware that our results crucially depend on this choice, to the extent that the test parton can not only loose energy in an unstable plasma, but could also gain the energy, depending on how the initial conditions are chosen. Therefore, the results presented in [21][22][23][24] do not reveal the full complexity of the problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in this paper have been used extensively in our analysis of parton energy loss in unstable QGP, a preliminary account of which is published as Refs. [19][20][21]. We hope that the analysis we have presented in this paper will facilitate computations of other characteristics of anisotropic QGP.…”
Section: Summary and Final Remarksmentioning
confidence: 99%
“…[9,[15][16][17][18]. A particularly interesting quantity is the energy loss of a highly energetic parton traversing an unstable QGP, which depends crucially on the spectrum of collective excitations (a preliminary account of our energy-loss study can be found in [19][20][21]). Complete information about the collective modes of an anisotropic system is therefore important and useful.…”
Section: Introductionmentioning
confidence: 99%